A STRATEGIC VIEW OF MINILATERALISM: INDONESIA, QUAD, ASEAN, SOUTH KOREA, JAPAN, AND IMPEDIMENT TO ASEAN CENTRALITY? - Hino Samuel Jose; Sigit Aris Prasetyo (Jurnal Ilmiah Kajian Keimigrasian, 2021)
This paper elaborates on how Indonesia and ASEAN could synergize their role on a more strategic views in ensuring ASEAN-led centrality. With minilateralism concerns growing, this paper addresses the importance of maintaining external relations for constructive dialogue and how foreign policy restructurization of Indonesia should be executed in a more normative and ideational level. This paper employs qualitative analysis through document-based research on previous literatures to formulate the contention and discussions that has been very Comprehensive and wide in scholarly analyses. Will Indo-Pacific prevail with ASEAN as the central player? What Jakarta has to do about it?